MICROPROPAGATION AND ACCLIMATIZATION OF Hyptis pectinata ACCESSIONS - FEITOSA, ROSANA BARROSO; SANTOS, MARIA CLEZIA DOS; SANTOS, MARIANA DE SOUZA; ARRIGONI-BLANK, MARIA DE FÁTIMA; BLANK, ARIE FITZGERALD (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
Hyptis pectinata is an important specie with a wide use in the Brazilian northeast in treatments of bacterial infections, pain and inflammation. In this work, different experiments were performed in order to establish a micropropagation protocol for H. pectinata accessions. For plantlets acclimatization, substrates containing coconut powder and/or vermiculite supplemented with limestone and/or NPK (3-12-6) fertilizer, and/or MS medium salts were used. SAM-016, SAM-017 and SAM-018 accessions may be micropropagated in 50% MS salts without growth regulators. Plantlet acclimatization may be obtained using the substrate containing coconut powder + 1 g L-1 limestone + MS salts.